Psycholinguistics-Based Creative Writing to Optimize Literacy Skills in Elementary Schools - Maria Ulfa; Eva Oktaviana; Nur Hasanah (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2026)
Human beings, language, the psyche, and cognitive abilities form an inseparable unity intertwined through creativity. The product of this synthesis is poetry. Poetry represents the soul of human cognition and creativity expressed through language. It consists of themes, diction, metaphors, and layers of meaning. As a result of this cognitive process, poetry can be utilized to enhance literacy skills. This qualitative descriptive study with content analysis analyzed poems written by 61 fifth-grade students at SDN Klender 03, East Jakarta. The analysis employed the Miles and Huberman flow model, consisting of three stages: data reduction, data display, and data verification. The students’ poems were examined in terms of theme, diction, metaphor, and complexity of meaning. Based on the findings, the analysis applied a psycholinguistic approach. The study revealed that students’ writing patterns tended to involve imitation, indicating the need for poetry writing instruction that concretizes students’ thoughts one of which can be stimulated through visual imagery. Effective poetry writing instruction can stimulate students’ creative thinking skills and, consequently, foster literacy skills more effectively.